Sensitivity analysis of solute kinetics in a four compartmental model for hemodialysis patients - Munir, Mohammad; Usman Saleem Khan Panni; Nasreen Kausar; Rukhshanda Anjum (Kuwait Journal of Science, 2021)
Sensitivity Analysis of the most advanced four compartmental mathematical model explaining solute kinetic in the hemodialysis patients was performed on the basis of the data collected from six patients with different BMIs. The toxin concentration in all compartments increases with the decrease in the BMIs of the patients. The clearance rate, k_clear, and the volume of extracellular compartment, V_E, are the most sensitive while the volume of the muscle tissue compartment, V_MT , and the clearance rate, k_MT , are the least sensitive parameters during dialytic interval. The production rate, G, and the volume of the extracellular compartment, V_E, are the most sensitive while kclear and k_EAT are the least sensitive parameters of all parameters during the interdialytic interval. The overall production rate, G, remains more sensitive than the clearance rate, k_clear during one complete cycle.